Importancia del aula virtual para la enseñanza aprendizaje de los niños y niñas de la escuela de educación general básica “Abdón Calderón”, de la parroquia Alaquez, cantón Latacunga - Taipe Jácome, José Kleber (2015)
The objective of the present investigative work is: “To propose the use of a virtual classroom in order to improve the teaching-learning process in the children OF THE Abdón Calderon Basic Education School, Alaquez Parish, Latacunga during the 2014-2015 academic year”. The problem, which was investigated, was what is the importance of a virtual classroom for the teaching - learning in the children? The methods that were used were: the deductive method for the development of the theoretical background making emphasis in the fundamental categories; the synthetic method was applied in the study of the investigation antecedents and the analytical one was applied at the moment of applying and interpret the results. The discovered conclusions were: there is a lack of knowledge about technological tools, the virtual classroom could improve the teaching-learning process and it is important to have the availability of a manual. The established proposal as an alternative of a solution is the elaboration of a manual on the training about virtual classroom aimed at the teachers of the institution.